2016
DOI: 10.1139/cgj-2015-0177
|View full text |Cite
|
Sign up to set email alerts
|

Field study of residual forces developed in pre-stressed high-strength concrete (PHC) pipe piles

Abstract: A large-scale field testing program for the study of residual forces in pre-stressed high-strength concrete (PHC) pipe piles is presented in this paper. Five open-ended PHC pipe piles with 13 or 18 m in embedded length were installed and used for static loading tests at a building site in Hangzhou, China. All the piles were instrumented with fiber Bragg grating (FBG) strain gauges. The residual forces in these piles were recorded during and after installation. The measured load transfer data along a pile durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…
We thank the Discussers for their interest in our paper (Kou et al 2016). We agree that the jacking of adjacent piles could cause a tensile effect when the center-to-center distance between two adjacent piles is small.
…”
mentioning
confidence: 56%
“…
We thank the Discussers for their interest in our paper (Kou et al 2016). We agree that the jacking of adjacent piles could cause a tensile effect when the center-to-center distance between two adjacent piles is small.
…”
mentioning
confidence: 56%
“…With the development of marine economy and high-speed traffic engineering in the 21st century, offshore engineering and high-speed railways and expressways, which can bear complicated loads such as wind, wave, and traffic for a long time, have put forward higher requirements for pile foundations [5][6][7][8]. Prestressed high-strength concrete (PHC) pipe pile has been widely used for its advantages of convenient construction, high bearing capacity, reliable quality, and short molding and curing time [9,10]. Plie jacking produces less noise and vibration, less air pollution, and does not affect the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…A number of field and model tests were conducted to study the effect of soil plugging on the behaviour of open-ended piles jacked into sand [12]. Kou et al [13,14] revealed that the loading-settlement behavior was closely related to the development of soil plugs. Yu and Yang [15] compared major open-ended pipe pile design methods and proposed the Hong Kong University (HKU) method to estimate the end bearing capacity of open-ended steel piles in sand based on the Imperial College Pile (ICP) and the University of Western Australia (UWA) methods [16,17].…”
Section: Introductionmentioning
confidence: 99%